Spousal Choice among the Children of Turkish and Moroccan Immigrants in Six European Countries: Transnational Spouse or Co-ethnic Migrant? - Sarah Carol; Evelyn Ersanilli; Mareike Wagner (International Migration Review, 2014)
Transnational marriages of migrants in Western Europe tend to be seen as hampering integration. In response, policies have been tightened, despite little knowledge on transnational marriages and the effects of such measures. This paper investigates the role of individual preferences and contextual factors such as family reunification policies, group size and development levels of the regions of origin in partner choice of the children of Turkish and Moroccan immigrants. We draw on a novel dataset collected in Austria, Belgium, France, Germany, the Netherlands, and Sweden. Our findings suggest that transnational marriages are partly associated with contextual factors such as a rural origin and family reunification policies. The analysis indicates higher rates of transnational marriages under open family reunification policies, providing tentative evidence of policy effects. On the individual level, the choice of a partner from the parents' origin country is associated with religiosity.
Keywords: 300